Sensory Activation of Command Cells for Locomotion and Modulatory Mechanisms: Lessons from Lampreys - Daghfous, Gheylen; Green, Warren W.; Alford, Simon T.; Zielinski, Barbara S.; Dubuc, Réjean (Frontiers in Neural Circuits, 2016)
Sensorimotor transformation is one of the most fundamental and ubiquitous functions of the central nervous system. Although the general organization of the locomotor neural circuitry is relatively well understood, less is known about its activation by sensory inputs and its modulation. Utilizing the lamprey model, a detailed understanding of sensorimotor integration in vertebrates is emerging. In this article, we explore how the vertebrate central nervous system integrates sensory signals to generate motor behavior by examining the pathways and neural mechanisms involved in the transformation of cutaneous and olfactory inputs into motor output in the lamprey. We then review how 5-HT acts on these systems by modulating both sensory inputs and motor output. A comprehensive review of this fundamental topic should provide a useful framework in the fields of motor control, sensorimotor integration and neuromodulation.